The XXI century guidance and its social responsibility - Vallejo, Grisel (2008)
This paper aims to consider the XXI century guidance in Venezuela as a discipline with a high social commitment. As a program, must now be redefined in order to push for proposals leading to the inclusion of all those people, who have traditionally been excluded because of their race, ethnicity, gender or physical disability and social praxis as is aimed at facilitating the processes of human development dimensions of Being, Living, Serving, Knowing and Doing in the personal, family and community along the continuum of life, The skills acquired through the processes of guidance, are determinants to provide the means for citizens to manage their own and their community development. It is the need for a paradigm shift that leaves behind the classic position of a counselor who helps others, from it he has experience and thus will help. It rather suggests a relationship of intersubjective guidance. On the other hand, it is the need to strengthen the social capital of the spaces that contextualize the process. It also explains the scope of the National Guidance System.